Association Between Hypertension Management Education and Multiple Healthy Behaviors: A Cross-Sectional Study. Issue 6 (July 2022) - Kim, Bomgyeol; Jang, Sung-In; Kim, Do Hee; Lee, Sang Gyu; Kim, Tae Hyun
Purpose: This study aimed to evaluate the association between hypertension management education and the adoption of multiple healthy behaviors. Design: Cross-sectional study. Setting: Data from the 2019 Community Health Survey in Korea. Subjects: Of the 213, 900 participants in the 2019 database, 89, 773 (42.0%) were hypertensive and 124, 127 (58.0%) were normotensive. Measures: Secondary data analysis included a 1:1 computer-assisted personal interview. "Multiple healthy behaviors" included not smoking, not drinking excessively, and walking briskly. "Hypertension management education" referred to information on hypertension management that participants received from clinics, hospitals, and public health centers, outside consultation with a doctor. Analysis: The association between hypertension management education and the adoption of multiple healthy behaviors was evaluated using multiple logistic regression. Results: In total, 89, 773 (42.0%) participants were hypertensive. Among 61, 589 patients with diagnosed hypertension, only 7, 719 (12.5%) received hypertension management education. Participants who received such education were more likely to adopt multiple healthy behaviors (odds ratio [OR] = 1.27, 95% confidence interval [CI]: 1.21–1.34) than their counterparts (OR = 0.91, 95% CI: 0.89–0.93). Participants with undiagnosed hypertension were least likely to adopt multiple healthy behaviors (OR = 0.89, 95% CI: 0.86–0.92). No causal relationships were ascertained because of the cross-sectional study design. Conclusions: Education can improve the adoption of multiple healthy lifestyles among hypertensive patients. Patients should be encouraged to participate in hypertension management education.